The Anticancer Activity of Marine Sponge Cinachyrella sp. (Family Tetillidae) - Nurhayati, Awik Puji Dyah; Pratiwi , Rarastoeti; Istriyati; Wahyuono, Subagus; Voogt, Nichole J de (IPTEK The Journal for Technology and Science, 2025)
Cinachyrella sp. marine sponge produce many kinds of secondary metabolites. The purpose of this study was to examine the cytotoxic and anti-proliferative activity of marine sponge Cinachyrella sp. The sponge was extracted with 96 % ethanol. Ethanol extract cytotoxicity assay were performed with MTT method (Microculture Tetrazolium) against cell lines of HeLa, T47D, WiDr and Vero. The results show that the ethanol extract was only toxic to cell lines of HeLa with IC50 897.809 ug/mL but did not toxic to cell lines of T47D, WiDr and normal cell lines of Vero. Fractionation of the ethanol extract was conducted by Vacuum Column Chromatography (VCC) and had 4 fractions, which were F1, F2, F3 and F4. Cytotoxicity and cell proliferation inhibitory were tested on fractions F1, F2, F3 and F4 against cell lines of T47D. The IC50 values of F1; F2; F3 and F4 against cell lines of T47D were 82.744; 163.679; 66.522 and 333.026 ug/mL respectively, and fraction F3 concentration 31.5 ug/mL inhibits cell proliferation of T47D cell lines at 48 hours of incubation.